2019
DOI: 10.1002/jbm4.10189
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Osteosclerosis by Inoculated Cd133+ PC3 Cells in Bone‐marrow Microenvironmental Niches

Abstract: Bone is the most common site of prostate cancer (PC) metastasis. Studies suggest that cancer stem cells (CSCs) are associated with stemness characteristics, providing some support for the concept that CSCs act as osteosclerotic precursors in bone microenvironmental niches. Here, we asked whether ectopic overexpression of CD133 maintains stability of CSCs in human PC cell lines and induces the changes of molecular features in the bone microenvironment. Ectopic overexpression of CD133 in PC3 or DU145 cells led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…It was reported that galectin-3, a tumor-secreted sugar-binding protein, regulates the expression of Osx, thereby remodeling bone in the bone microenvironment niche ( Nakajima et al, 2014 ). Opn released from cancer stem cells acts as a stimulator of osteogenesis by regulating Osx ( Kim et al, 2019 ). In addition, expressions of two cytokines, interleukin-8 (IL-8) and parathyroid hormone-related protein (PTHrP), that cause bone destruction by inducing osteoclast differentiation and activation, were increased by Osx over-expression.…”
Section: Other Factors In the Bone Microenvironment Interact With Osxmentioning
confidence: 99%
“…It was reported that galectin-3, a tumor-secreted sugar-binding protein, regulates the expression of Osx, thereby remodeling bone in the bone microenvironment niche ( Nakajima et al, 2014 ). Opn released from cancer stem cells acts as a stimulator of osteogenesis by regulating Osx ( Kim et al, 2019 ). In addition, expressions of two cytokines, interleukin-8 (IL-8) and parathyroid hormone-related protein (PTHrP), that cause bone destruction by inducing osteoclast differentiation and activation, were increased by Osx over-expression.…”
Section: Other Factors In the Bone Microenvironment Interact With Osxmentioning
confidence: 99%
“…Survival of PCSCs could promote tumor initiation, migration, and relapse, and induce therapy resistance ( 10 , 11 ). In addition, PCSC plasticity is anticipated to play a pivotal role in bone metastases of prostate cancer ( 12 ). PCSCs can be identified with cell surface markers expressed, and studies suggest that CD44 harbors them to exhibit tumor invasive properties ( 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…5−7 In fact, the plasticity of PCSCs essentially plays a bigger part in bone metastases of PCa. 8,9 Furthermore, not all CSCs are the same in their morphology, capabilities, or characteristics, as CSCs are heterogeneous. As tumor spheroids develop, CSCs reprogram themselves to become increasingly heterogeneous, making it difficult to target then.…”
Section: Introductionmentioning
confidence: 99%
“…PCSCs are distinguished from PCa cells by their ability to differentiate uncontrollably, self-renewability, stemness, and quiescence. On the other hand, cancer stem cells (CSCs) divide symmetrically to produce a clone of two CSCs or asymmetrically to produce one CSC and another differentiated form that becomes part of the tumor. , Although evidence suggests the origin of CSCs, its ability to initiate tumors, or the degree to which CSCs can influence tumorigenesis is uncertain, and studies have shown that CSCs are involved in tumor relapse, migration, and resistance toward therapy. In fact, the plasticity of PCSCs essentially plays a bigger part in bone metastases of PCa. , …”
Section: Introductionmentioning
confidence: 99%